Targeting MetaLnc9/miR-143/FSCN1 axis inhibits oxidative stress and myofibroblast transdifferentiation in oral submucous fibrosis - Ming-Yi Lu; Pei-Ling Hsieh; Shih-Chi Chao; Chih-Yuan Fang; Yoichi Ohiro; Yi-Wen Liao; Cheng-Chia Yu; Min-Te Chang (Elsevier, 2024)
Background/purpose: Persistent activation of myofibroblasts is attributed to various dysregulated biological events conferring multiple types of fibrosis diseases, including oral submucous fibrosis (OSF). Although the significance of non-coding RNAs (ncRNAs) in the occurrence of fibrosis has been appreciated, the detailed mechanisms still have not been fully elucidated. The aim of this study was to identify key dysregulated ncRNAs and elucidate their pro-fibrotic mechanisms in promoting myofibroblast activation and the pathological development of OSF. Materials and methods: Expression of non-coding RNAs and mRNAs in OSF cohort was determined using RNA sequencing and qRT-PCR. The molecular axis of pro-fibrotic ncRNAs were exploited via luciferase reporter activity assay and RNA expression rescue experiments. Functional assays, including collagen gel contraction, wound healing ability, cell migration, and reactive oxygen species (ROS) production, were conducted to assess the changes in the myofibroblastic phenotypes of primary human buccal mucosal fibroblasts. Results: Herein, we found that long non-coding RNA MetaLnc9 was upregulated in OSF specimens and positively associated with several fibrosis markers. Silencing of MetaLnc9 diminished the features of activated myofibroblasts and the production of ROS. We not only showed that MetaLnc9 functioned as a competitive endogenous RNA of microRNA (miR)-143, but also demonstrated that the pro-fibrosis effect of MetaLnc9 on myofibroblast activities was mediated by suppression of miR-143. Moreover, our data showed that fascin actin-bundling protein 1 (FSCN1) was a direct target of miR-143 and positively related to MetaLnc9. Conclusion: Upregulation of MetaLnc9 may enhance the activation of myofibroblasts by sponging miR-143 and titrating its inhibitory property on FSCN1.